2015
DOI: 10.1007/s10664-015-9378-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparing and experimenting machine learning techniques for code smell detection

Abstract: Several code smell detection tools have been developed providing different results, because smells can be subjectively interpreted, and hence detected, in different ways. In this paper, we perform the largest experiment of applying machine learning algorithms to code smells to the best of our knowledge. We experiment 16 different machine-learning algorithms on four code smells (Data Class, Large Class, Feature Envy, Long Method) and 74 software systems, with 1986 manually validated code smell samples. We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
87
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(147 citation statements)
references
References 54 publications
0
87
0
3
Order By: Relevance
“…To get a high number of conflicts we selected with the "Law of Demeter" a rather rigid design smell definition, ignored weaker variations and did not invest in perfecting the definition upfront. As an evaluation of the "Law" it would be utterly 3 We use here a term first suggested by Karl R. Popper in 1939. He states: "Instead of discussing the 'probability' of a hypothesis we should try to assess what tests, what trials, it has withstood; that is, we should try to assess how far it has been able to prove its fitness to survive by standing up to tests.…”
Section: The "Law Of Demeter" / "Law Of Good Style"mentioning
confidence: 99%
See 2 more Smart Citations
“…To get a high number of conflicts we selected with the "Law of Demeter" a rather rigid design smell definition, ignored weaker variations and did not invest in perfecting the definition upfront. As an evaluation of the "Law" it would be utterly 3 We use here a term first suggested by Karl R. Popper in 1939. He states: "Instead of discussing the 'probability' of a hypothesis we should try to assess what tests, what trials, it has withstood; that is, we should try to assess how far it has been able to prove its fitness to survive by standing up to tests.…”
Section: The "Law Of Demeter" / "Law Of Good Style"mentioning
confidence: 99%
“…We relied on the Sharma and Spinellis survey as our key witness for the relevance of the question of high rates of false positives. A more thorough discussion of the work on false positives would be very desirable, especially with respect to those publications that made the effort to construct manually validated datasets [3,28,29].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Arcelli Fontana et al [5,31] and Kessentini et al [16,48,49,97] used machine learning and search-based algorithms to discover code smells, pointing out that a training set composed of one hundred instances is sufficient to reach very high values of accuracy. Nevertheless, Di Nucci et al [25] recently showed that the performance of such techniques may vary depending on the exploited dataset.…”
Section: Code Smell Detection and Prioritizationmentioning
confidence: 99%
“…In this approach, code smells are detected as agglomerations, unlike our work, where we focus on strategies that identify code smells individually. Another study by Fontana et al, (2015) applied 16 different machine-learning algorithms in 74 software systems to detect four code smells in an attempt to avoid some common problems of code smell detectors.…”
Section: Related Workmentioning
confidence: 99%